2017
DOI: 10.5114/reum.2017.66686
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermal imaging in connective tissue diseases

Abstract: Infrared thermal imaging (IRT) is a non-invasive, non-contact technique which allows one to measure and visualize infrared radiation. In medicine, thermal imaging has been used for more than 50 years in various clinical settings, including Raynaud’s phenomenon and systemic sclerosis. Imaging and quantification of surface body temperature provides an indirect measure of the microcirculation’s overall performance. As such, IRT is capable of confirming the diagnosis of Raynaud’s phenomenon, and, with additional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 18 publications
0
24
0
9
Order By: Relevance
“…IRT is a simple non-contact, non-invasive imaging technique that provides an accurate quantitative measurement of surface body temperature. IRT has shown promise in several studies as a potential screening tool for the diagnosis of health conditions affecting the hands and digits [Chojnowski, M., 2017], including Raynaud's phenomenon [Ismail et al 2014] and systemic sclerosis [Murray et al 2009]. Although the results of this study have highlighted the potential of IRT as means of quantifying changes in surface temperature of the hands under hypoxic conditions of high altitude, there are several limitations to IRT that have hampered its clinical application to date; including the lack of standardised protocols, the calibration of the equipment, and the accuracy of the temperature readings that only provide an indirect measurement of tissue perfusion [Chojnowski, M., 2017].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IRT is a simple non-contact, non-invasive imaging technique that provides an accurate quantitative measurement of surface body temperature. IRT has shown promise in several studies as a potential screening tool for the diagnosis of health conditions affecting the hands and digits [Chojnowski, M., 2017], including Raynaud's phenomenon [Ismail et al 2014] and systemic sclerosis [Murray et al 2009]. Although the results of this study have highlighted the potential of IRT as means of quantifying changes in surface temperature of the hands under hypoxic conditions of high altitude, there are several limitations to IRT that have hampered its clinical application to date; including the lack of standardised protocols, the calibration of the equipment, and the accuracy of the temperature readings that only provide an indirect measurement of tissue perfusion [Chojnowski, M., 2017].…”
Section: Resultsmentioning
confidence: 99%
“…IRT has shown promise in several studies as a potential screening tool for the diagnosis of health conditions affecting the hands and digits [Chojnowski, M., 2017], including Raynaud's phenomenon [Ismail et al 2014] and systemic sclerosis [Murray et al 2009]. Although the results of this study have highlighted the potential of IRT as means of quantifying changes in surface temperature of the hands under hypoxic conditions of high altitude, there are several limitations to IRT that have hampered its clinical application to date; including the lack of standardised protocols, the calibration of the equipment, and the accuracy of the temperature readings that only provide an indirect measurement of tissue perfusion [Chojnowski, M., 2017]. However, despite these limitations, the potential applications of IRT as a diagnostic adjunct to existing telemedicine services should not be overlooked, and further assessment of its clinical applicability to the diagnosis and classification of frostbite and cold-related injuries should be explored further.…”
Section: Resultsmentioning
confidence: 99%
“…e application of thermal imaging is persistently developing along with the technical advancements. ermal imaging is used to evaluate dry eye [23], lower and upper extremities [24,25], dermatology [26], Raynaud's disease [27,28], diabetic foot ulcer [29], stress [30], and atherosclerosis [31].…”
Section: Introductionmentioning
confidence: 99%
“…Review articles on IT provide either favorable 27,28 or unfavorable 29,30 feedback about its applicability for mass screening. The favorable reviews suggest that for certain applications, thermal imaging is shown to provide objective measurement of temperature changes that are clinically significant for the detection of local inflammatory processes, skin lesions, benign and malignant tumors, vasoactivity, and vascular diseases.…”
mentioning
confidence: 99%